A Virtual Reality Supported Approach to Occupancy Engagement in Building Energy Design for Closing the Energy Performance Gap. (2015) - Niu, S.; Pan, W.; Zhao, Y.
Abstract: There is a trend in the world to adopt low or zero carbon building design principles and technologies. However, energy performance gap is a significant barrier to the development of low or zero carbon buildings. A predominant reason of the performance gap is the insufficient consideration of residents' needs, which may lead to subsequent inappropriate user behaviours. Previous research on energy-related occupant behaviour is built either on statistical analysis from post-occupancy evaluations or stochastic models. There is a lack of pre-occupancy measurement of the interaction between occupant behaviour and building design alternatives. This paper aims to develop an innovative analytic approach using virtual reality (VR) technology to help building designers (architects, system engineers and interior designers) to identify the design pattern which guides the occupants to behave in the most energy-efficient way, so as to closing the energy performance gap resulting from occupants' misconduct. The paper presents a VR-assisted innovative occupant-engaged framework in building energy design based on Design with Intent (DwI) method. Then the approach is validated by a case study on lighting control design for a sample residential building project in Hong Kong. The combination with decision-making is recommended for further research.